2010
DOI: 10.1118/1.3358123
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of hemodynamic changes induced in the healthy breast through inspired gas stimuli with MR-guided diffuse optical imaging

Abstract: Purpose: The modulation of tissue hemodynamics has important clinical value in medicine for both tumor diagnosis and therapy. As an oncological tool, increasing tissue oxygenation via modulation of inspired gas has been proposed as a method to improve cancer therapy and determine radiation sensitivity. As a radiological tool, inducing changes in tissue total hemoglobin may provide a means to detect and characterize malignant tumors by providing information about tissue vascular function. The ability to change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…6(b)] breasts. Considering the results we obtained in our previous study without feedback control of the inspired gas mixture based on end-tidal measurements, 11,14 this outcome may be due to StO 2 changes involving both Hb and HbO, but with some phase delay between the Hb and HbO alterations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6(b)] breasts. Considering the results we obtained in our previous study without feedback control of the inspired gas mixture based on end-tidal measurements, 11,14 this outcome may be due to StO 2 changes involving both Hb and HbO, but with some phase delay between the Hb and HbO alterations.…”
Section: Discussionmentioning
confidence: 99%
“…As opposed to otherwise administering inhaled gas mixtures (where a poor relationship exists between the exhaled gas concentrations and those in the blood), [11][12][13][14][15] end-tidal (i.e., exhaled gas) partial pressures were controlled, and these quantities have been shown to be surrogates for those in the arterial blood (allowing the arterial blood partial pressure to be monitored and controlled during NIRS imaging for the first time). The results in Figs.…”
Section: Discussionmentioning
confidence: 99%
“…We evaluated four stimulus paradigms, comprising carbogen and “carbogen‐light” interleaved with either medical air or oxygen relative to an all‐air control state. This investigation builds on previous work to optimize detection of vasomotor response in the breast via T 2 ‐based BOLD contrast,15 as it accounts for normal physiological variations in each subject, which is a confounding factor in these types of analyses 16. We also evaluated the efficacy of a lower (2%) CO 2 carbogen variant for inducing a vasomotor response, as previous studies have reported that subjects found this variant easier to breathe 24.…”
Section: Discussionmentioning
confidence: 98%
“…Carpenter et al similarly reported that 20% of volunteers breathing air vs. carbogen and 19% breathing oxygen vs. carbogen did not demonstrate a significant effect above natural background fluctuations, likely due to metabolic variations acting independently of the respiratory stimulus 16. The ability to detect a significant BOLD response appears to vary with menstrual cycle changes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation